PENGARUH PEMBERIAN EFFLEURAGE MASSAGE AROMATHERAPHY LAVENDER TERHADAP KUALITAS TIDUR MALAM IBU HAMIL PRIMIGRVIDA TRIMESTER III DI KLINIK BIDAN MANDIRI DOMINGAS SURABAYA - Arkha Rosyaria Badrus; Miftahul Khairoh (Jurnal MIDPRO, 2018)
A mid the high AKI and this AKB, it needs to be drawn red thread from the base of the problem, namely the welfare of pregnant women. From there, researchers have the idea to conduct scientific experiments using eufflurage massage with the aroma of lavender teraphy as a stimulation of the peripheral nerves and central nerves to produce and release the hormone endorphins. Predicted 78 percent of women have difficulty falling asleep during pregnancy. Physical and hormonal changes, causing discomfort to cause less sleep. One of the causes of sleep disorders of the third trimester pregnant women is back pain, frequent urination and anxiety before labor. Place of research conducted at Dominga’s independent clinic followed by home visit given 7 days treat with frequency 15 minutes Massage. Research using pre experimental approach with pre and post test without control. The research designs undertaken in the study were measurement of Sleep Quality with The Pittsburgh Sleep Quality Index (PSQI). The resulting data is not normally distributed, the statistical test using Mc Nemar test obtained p: 0.004 <0.05 and the value of Z arithmetic 0.774 <1.96 then Ho rejected and Ha received due to endhorpin hormone that can provide relaxation in pregnant women third trimesterKeywords: Massage Effleurage, Night Sleep Quality Pregnant Trimester III